Reading Russian poetry: An expert-novice study - Danil Fokin; Stefan Blohm; Elena Riekhakainen (Bern Open Publishing, 2022)
Studying the role of expertise in poetry reading, we hypothesized that poets' expert knowledge comprises genre-appropriate reading- and comprehension strategies that are reflected in distinct patterns of reading behavior. We recorded eye movements while two groups of native speakers (n=10 each) read selected Russian poetry: an expert group of professional poets who read poetry daily, and a control group of novices who read poetry less than once a month. We conducted mixed-effects regression analyses to test for effects of group on first-fixation durations, first-pass gaze durations, and total reading times per word while controlling for lexical- and text variables. First-fixation durations exclusively reflected lexical features, and total reading times reflected both lexical- and text variables; only first-pass gaze durations were additionally modulated by readers' level of expertise. Whereas gaze durations of novice readers became faster as they progressed through the poems, and differed between line-final words and non-final ones, poets retained a steady pace of first-pass reading throughout the poems and within verse lines. Additionally, poets' gaze durations were less sensitive to word length. We conclude that readers' level of expertise modulates the way they read poetry. Our findings support theories of literary comprehension that assume distinct processing modes which emerge from prior experience with literary texts.